Polémica: do posicionamento à referenciação, passando pelas emoções - Gil, Isabel Fuzeta (Revista da Associação Portuguesa de Linguística, 2022)
In this article we analyse the enunciative-pragmatic and rhetorical strategies that globally shape discourses in the context of a polemical discursive event, drawing on Amossy’s (2014) definition of polemics. From a corpus consisting of transcripts of debates in the Assembly of the Republic and press texts between 2018 and 2021, we approach, from an argumentative, rhetorical and pragmatic-discursive perspective, the global configuration of discourses that have euthanasia as their object. Euthanasia emerges as a source of polemic in the context of the discussion of several bills aimed at its legalization in parliament. In a particularly agonistic context raised from the outset by the topic at the core of the debate, one of the objectives of this analysis cannot but analyse the referentiation of the way concept of “euthanasia”: the various ways of referencing are one of the rhetorical-argumentative and discursive strategies that comes to the fore, given the role of implicitations, beliefs and common knowledge in the addressee’s response. The referentiation of the discursive object 'euthanasia' is therefore of particular interest, since it mirrors an axiological hierarchy of values, encyclopedic knowledge, doxal voices supporting different ideological positions, particularly in an agonal discourse around eventual decisions with (bio)ethical, religious and sociological implications. For the analysis of the referentiation of 'euthanasia' and other terms associated with it, revealing different positions and points of view, we rely on studies by Angenot (2014), Sitri (2003, 2004), Mondada (2002), amongst others. Closely connected with the conceptualization of “euthanasia”, one finds discursive traces of pathemization contributing to the ultimate purpose of the speakers' macro-illocutionary act. Since nowadays it is widely accepted that discourse has an emotional (or pathemic, according to Charaudeau) aspect, our objective is also to observe how emotions are interwoven — and justified — in the thread of discourses. Given the controversial nature of the topic under discussion, we found that the discourse(s) are the target of a process of pathemization and spectacularization (Charaudeau, 2000, 2005). The appeal to emotions, in particular to pity / compassion, is imbricated in the logos, in such a way that the dimension of pathos is intended to be validated and justified (Micheli, 2008, 2010). On the other hand, the "good reasons" (Plantin, 2011) at the base of the pathemic dimension of the discourse are indelibly linked to the construction of an ethos favorable to the Speaker and the capture of the addressee and a vast group auditorium. In the wake of Kerbrat-Orecchioni (1980), we are interested in analyzing the marks of polemicity that translate into enunciative-pragmatic strategies summoned as a support for the argumentative activity. We thus resume some aspects in the analysis of polemics already addressed in Gil (2013, 2017, 2021).